Herbicida Metolaclor aplicado en preemergencia y presiembra incorporada, para el control de malezas en maíz (Zea mays) en la zona de Puebloviejo - Guzmán Escobar, Freddy Wladimir (2017)
VIII. SUMMARY This research work was carried out in the canton of Puebloviejo, Province of Los Ríos, on the Pan-American Highway and on August 10, in the lands owned by Mr. José Lautaro Guzmán Urrea. The terrain is with geographic coordinates 06063'594 of south latitude and 98028'728 of longitude west and a height of 8msnm. The objectives were to determine the optimal application rate of Metolachlor herbicides for weed control in maize; Identify the most appropriate application time and analyze the treatments economically. DK 7088 hybrid was used as the seed material. Seven treatments were studied, with the doses of herbicide Metolaclor at doses of 0.90; 1.25; 1.80 L / ha in pre-emergence and 2.50; 3.00 and 3.50 L / ha in built-in preseeding and a mechanical control to which manual weeding was performed. The experimental design applied was Completely Random Blocks, with seven treatments and three replicates. To estimate the comparison of the averages, the Tukey test was performed at 95% probability. During the development of the experimental work the preparation of the ground was carried out; sowing; Weed control, irrigation, fertilization, pest and disease control, and harvesting. To estimate the effects of the treatments, the selectivity data of the herbicide were taken at 7 and 14 days; Weed control at 14 and 21 days after application of the herbicide; Plant height; Length and diameter of the ear; Number of grains per ear; 1000 grains weight; Performance and economic analysis. The results showed that the highest toxicity of the herbicide was observed in the application of the herbicide Metolaclor in doses of 3.0 and 3.50 L / ha in the pre-plant, which consequently influenced that these treatments register excellent control of Weeds; The height of plant was superior in the treatments that the application in the pre-plant was carried out; The length and diameter of ear was higher in the treatments that the herbicide Metolaclor was used in doses of 3.50 L / ha in incorporated pre-plant; The use of the herbicide Metolaclor at doses of 1.25 L / ha in preemergence reflected a higher number of grains / ear and 1000 grains weight and the higher yield and economic analysis was presented with the dose of 0.90 L / ha in preemergence of Herbicide Metolachlor with 7323.2 kg / ha and $ 965,38.